Posttraumatic Delayed Enophthalmos: Analogies with Silent Sinus Syndrome? Case Report and Literature Review. Issue 3 (September 2015) - Canzi, Gabriele; Morganti, Valeria; Novelli, Giorgio; Bozzetti, Alberto; Sozzi, Davide
Acute posttraumatic enophthalmos is a well-known symptom occurring in orbital blowout fractures. Its late onset in the absence of radiologic evidence of displaced fractures is rare and traditionally attributed to ischemic liponecrosis or fibrotic scarring of endo-orbital soft tissues. In this article, we describe a case of facial trauma, diagnosed and treated at the Maxillo-Facial Surgical Department of Hospital Ca' Granda Niguarda of Milan, in which delayed monolateral enophthalmos is associated with CT evidence of remodeling of orbital walls attributed to atelectasis of the maxillary sinus, as occurs spontaneously in patients suffering from silent sinus syndrome (SSS). Despite that classic criteria exclude traumatic etiology of SSS, recent literature suggests the possibility to include it. Our case is the first reported in literature supported by complete clinical and radiological documentation obtained before and after the condition established itself. The analogy with cases of spontaneous obstacle of aeration allows us to choose "two-step" surgical treatment with endoscopic uncinectomy and antrostomy and a delayed surgical correction of orbital volume to improve aesthetic results. The case described in this article and the review of the literature may focus physicians' attention on evaluating the possible traumatic changes in the physiologic sinus drainage system.